Analisis Faktor Yang Mempengaruhi Konsumen dalam Memilihan Jasa Pengiriman Barang Menggunakan Moda Kereta Api di Stasiun Madiun - Iswanto, Ary Putra; Puspitasari, Mariana Diah; Imron, Nanda Ahda; Kurniawan, Safrudin; Marsusiadi, Edi Nyoto Setyo; Nopriyanto, Windi; Ghifari, Muchammad Farhan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This study aims to determine the characteristics of users of goods delivery services by train at Madiun Station and to analyze the factors that influence the choice of goods delivery services by train at Madiun Station using the multinomial logistic regression analysis method. The results obtained are based on the characteristics of users of goods delivery services by train dominated by men with student status, last education is high school and monthly income is less than Rp. 1,000,000. Of the 5 factors studied, namely the price factor, location factor, security factor, timeliness factor and information availability factor. There are 4 factors that significantly influence the choice of shipping goods by train at Madiun Station, namely location factors, security factors, timeliness factors and information availability factors.